Kinerja Unit Kepatuhan Internal dalam Pengawasan di Kantor Pengawasan dan Pelayanan bea dan cukai Tanjungemas Semarang - Prety Y Ayuningtyas; Wiwik Widayati; Lusia Astrika (Journal of Politic and Government Studies, 2013)
Today, measuring employee performance becomes very important for management toevaluate the performance of the company and planning purposes in the future. Variousinformation has been compiled in order to do work that can be controlled and accounted for. Thisis done in order to achieve efficiency and effectiveness in all business processes. Demands ofsociety and the Government's commitment to conduct better service to the community has ledthe Ministry of Finance in particular the Directorate General of Customs and Excise (DJBC) toimplement bureaucratic reform program. One form of bureaucratic reform program is run by theformation DJBC Internal Compliance Unit with more specific characteristics of the internalcontrol employee performance and employee code of conduct in order to reform the bureaucracycan make changes to employee performance and behavior for the better and the creation of goodgovernment.Keywords: Bureaucratic Reform, the Performance Monitoring